2008
DOI: 10.1007/s11746-008-1327-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal and Degradation of Phorbol Esters during Pre‐treatment and Transesterification of Jatropha curcas Oil

Abstract: Phorbol esters present in Jatropha curcas oil are toxic when consumed and are co-carcinogens. These could be a potential constraint in the widespread acceptance of Jatropha oil as a source of biodiesel. Phorbol esters were quantified in the fractions obtained at different stages of oil pre-treatment and biodiesel production. During degumming some phorbol esters were removed in the acid gums and wash water. This implies that the use of these acid gums in animal feed is not possible and care should be taken when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 10 publications
2
42
0
1
Order By: Relevance
“…For example, curcin, a toxicant commonly found in J. curcas seed, is a ribosome inactivating protein which like most proteins could be denatured or experience loss of function at high temperatures. Also, high temperature of 260°C and 3 mbar has been reported to completely degrade phorbol esters present in J. curcas (Makkar et al, 2009).…”
Section: Acid Valuementioning
confidence: 99%
“…For example, curcin, a toxicant commonly found in J. curcas seed, is a ribosome inactivating protein which like most proteins could be denatured or experience loss of function at high temperatures. Also, high temperature of 260°C and 3 mbar has been reported to completely degrade phorbol esters present in J. curcas (Makkar et al, 2009).…”
Section: Acid Valuementioning
confidence: 99%
“…PE amounts in the culture medium were monitored and quantified using high-performance liquid chromatography HPLC 31 . Aliquots were loaded into an HPLC system equipped with the reversed-phase column LiChrospher 100 RP-18 5 μm, 250 4 mm id, Merck and separated at 25 at a flow rate of 1.3 mL/min using an acetonitrile-water gradient elution buffer.…”
Section: Analysis Of Pesmentioning
confidence: 99%
“…The rats fed with treated meals exhibited delayed mortality compared to untreated meal-fed rats. The phorbol ester content was analysed in fractions obtained at different stages of oil pretreatment and biodiesel production from the physic nut by Makkar et al (2009). Makkar et al observed that the phorbol esters were destroyed by the stripping process during biodiesel production.…”
Section: -Solutionsmentioning
confidence: 99%